Graphite cathode and anode becoming graphene structures after cycling based on graphite-based dual ion battery using PP14NTF2 - Li, Z.; Liu, Jian; Li, J.; Kang, F.; Gao, F. (Pergamon, 2018)
© 2018 Elsevier Ltd Herein, a novel graphite-graphite dual ion battery (GGDIB) based on N-butyl-N-methyl-piperidinium bis(trifluoromethyl sulfonyl)imide (PP14NTF2) ionic liquid room temperature ionic liquid electrolyte, using conductive graphite paper as cathode and anode material is developed. The working principle of the GGDIB is investigated by scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS), that is, the NTF2-anions and PP14+cations in the electrolyte are intercalated into the graphite electrode during the charging process, while the NTF2-anions and PP14+cations are released into the electrolyte from the graphite electrode during discharging process. Interestingly, it is found through transmission electron microscopy (TEM) analysis that the graphite cathode and anode electrode materials of this GGDIB can become a few layers of graphene structure after cycling. The electrochemical performance, especially the discharge capacity, is influenced by the phenomenon of self-discharge. This GGDIB also exhibits excellent electrochemical performance, that is, the discharge capacity is 78.1 mA h g-1at a current density of 20 mA g-1over a voltage window of 0.1–5.0 V. In addition, the pseudopotential behavior in the GGDIB is also studied by cyclic voltammetry (CV).